"Waste not and stay at home" evidence of decreased food waste during the COVID-19 pandemic from the U.S. and Italy. (1st May 2021) - Rodgers, Rachel F.; Lombardo, Caterina; Cerolini, Silvia; Franko, Debra L.; Omori, Mika; Linardon, Jake; Guillaume, Sebastien; Fischer, Laura; Tyszkiewicz, Matthew Fuller-
Abstract: The COVID-19 pandemic has profoundly disrupted household food purchasing and preparation, including elements identified as important drivers of household food waste. The two main aims of this study were (1) to examine changes in food waste behaviors since the start of the COVID-19 pandemic in the U.S. and Italy; and (2) to investigate potential predictors of food waste behavior, including avoidance of supermarkets, increased home cooking, and increased role of health concerns in food choices. A sample of n  = 478 (79% female) individuals from the U.S., mean (SD) age = 30.51 (10.85), and n  = 476 individuals from Italy, (78% female), mean (SD) age = 33.84 (12.86), completed an online survey between April 8th and April 28 th 2020. Just under half of respondents (49%) reported decreased food waste since the start of the pandemic. Rates were significantly higher among the U.S. sample (61.5%, n  = 294) compared to the Italian sample (38%, n  = 180). Controlling for the time since restrictions were introduced, age, gender, and perceived financial security, logistic regression revealed greater reduction in food waste since the beginning of the pandemic for U.S. individuals relative to participants from Italy (OR = 0.47, p  < .001). In addition, increased importance of health concerns when making food choices (OR = 1.34, p  < .005) as well as more frequent cooking (OR = 1.35, p  < .001), and greater avoidance of supermarkets (OR = 1.15, p  = .049) were associated with greater probability of less food waste. Scarcity and greater reliance on cooking may encourage individuals to reflect on food waste practices. Further research should explore how these factors may be targeted to reduce food waste beyond the pandemic.